When Corporations Changed Their Social Role—and Upended Our Politics - Lemann, Nicholas (Wall Street Journal - Online Edition, 2019)
Large companies once offered workers lifetime security and generous benefits. Then they stopped, setting the stage for our populist moment.
N/A
Keywords: DRUCKER; Peter; General Motors Co.; JENSEN; Michael C.; POLANYI; Karl; 1886-1964; WILSON; Charles Erwin; 1890-1961; domestic politics; elections; general news; international relations; national; political; politics; presidential elections; social role

What’s Missing - Navickas, Katrina (London Review of Books, 2018)
Capitalism is in crisis, again. Inequality, measured in wages, wealth distribution, employment, ‘affordable’ housing, has become the dominant framework for understanding the economy. Through this lens, people can extrapolate to the macroeconomic from their own individual experiences.
N/A
Keywords: MORAL Economists: R.H. Tawney; Karl Polanyi; E.P. Thompson & the Critique of Capitalism; The (Book); POLANYI LEVITT; Kari; POLANYI; Karl; 1886-1964; book review

Is Capitalism a Threat to Democracy? - Crain, Caleb (2018)
The idea that authoritarianism attracts workers harmed by the free market, a theory that emerged when the Nazis were in power, has been making a comeback.
N/A
Keywords: Can Democracy Survive Global Capitalism; KUTTNER; Robert; POLANYI; Karl; 1886-1964; capitalism; democracy; the populist temptation

The Great Transformer - Harrison, Roger Gran (American Interest, 2018)
N/A
Keywords: Great Transformation; The (Book); economic history; nonfiction; social history

How the market abandoned morality - Mason, Paul (New Statesman, 2018)
Like the lifelong sinner who makes a deathbed conversion, it was always likely that supporters of neoliberal globalisation would rediscover ethics towards the end. Having devastated communities through indifference, and coercively imposed commercial priorities on to family life, the political “centre” now has to deal with anger, distrust and rejection on an unmanageable scale. In The Future of Capitalism, Paul Collier, a former chief economist at the World Bank, now professor at the Oxford Blavatnik School of Government, attacks the twin ethical systems that have dominated policymaking in the free-market era: utilitarianism and the theories of social justice associated with the political philosopher John Rawls. In their place he outlines a project for the renewal of centrist politics based on communitarian ethics. The project, which he labels “hard centrism”, is backed by an appeal to patriotism and with a mea culpa from the economics profession. We over-egged the benefits of globalisation, trade, migration and light-touch regulation, and the result is an outbreak of fascism and xenophobia from Charlottesville to Katowice. If it were coherent, Collier’s solution might place him as the latest in a line of “moral economists”, broadly aligned with the centre left and stretching from RH Tawney in the 1920s, via Karl Polanyi to Edward Thompson, whose evolution is explored in Tim Rogan’s book The Moral Economists. Unfortunately, Collier’s solutions are not coherent, and about as likely to defuse populist anger as a Goldman Sachs away-day. Collier correctly identifies the symptoms that are driving political radicalisation: the massive inequalities generated by free-market economics; the spatial divide between ex-industrial towns, with their older and less educated workforce, and the buzzing, young cosmopolitan cities; plus the absence of empathy among those who’ve gained under neoliberalism for those who’ve lost out. But for Collier, the root cause of these malfunctions is not the structure of the neoliberal economy itself, nor the rapaciousness of a small financial elite. It is, instead, the rise of a new skilled and salaried middle class who can capture the economic and social gains generated by highly productive and asset-rich city economies. “The newly successful,” writes Collier, “are neither capitalists nor ordinary workers; they are the well educated with new skills. They have forged themselves into a new class, meeting at university and developing a new shared identity in which esteem comes from skill.” This group, says Collier, has not only captured policymaking but, to rub salt in the wound, developed an ideology whereby they – because of their mixed ethnicity and liberal sexuality – can portray themselves as victims in greater need of sympathy than the working poor, and at the same time justify their own lack of ethical belief. Collier’s identification of the urban salariat as a “new class” is not simply a metaphor. He classifies the typical behaviours of young, urban, educated people as economic “rent-seeking”, which, in traditional economics, refers to activities designed to increase your own wealth without increasing the wealth of society. It can range from property speculation to trying to rig government regulations to favour your firm. Collier, however, sees the lifestyle of educated urban people as the same kind of thing. Ducking and diving to get a decent job, investing in private tuition to improve your skills, “delaying marriage or delaying children” – each of these is portrayed as a form of exploitative behaviour, detrimental to the small-town poor, which must be discouraged by taxation and regulation. Just as Keynes wanted “euthanasia of the rentier”, Professor Collier wants fewer lawyers, fewer actors, fewer migrants and fewer people avoiding marriage and family life. If you are wondering what kind of politics emerges from all this, you will not be surprised to learn it is a form of social-democratic conservatism, severely critical of Bernie Sanders, Jean-Luc Mélenchon and Jeremy Corbyn – whose followers are written off as “youthful idiots”. Collier wants to save neoliberalism through a distributional attack on the urban salariat and a repudiation of its morality. So, although he wants to discourage high property values in cities, he is against rent control – which is too Marxist – and against a sudden programme of housebuilding, because it risks tanking house prices. To protect the political system from an enraged radical populace, Collier advocates depriving members of political parties from selecting who leads them – better that only elected representatives should have a say. There is a logic to the nostalgia. Since the most successful and inclusive form of capitalism in our lifetime was the communitarian statism of the 1950s and 1960s, to recreate it Collier argues we have to discourage the morality and lifestyle of educated, mercurial and seemingly amoral young people, limit the migration that is annoying low-skilled people, and promote the “ethical family” and patriotism as the roots of shared identity. But it is a doomed project. First, because it frames the task of renewing capitalism in opposition to the social values of the rising generation. Second, because, unlike the project of the radical left, which seeks to free the young generation from debt peonage and stagnating wages, Collier wants explicitly to penalise them until their behaviour falls into line with the communitarian project. Third, because it avoids the root of the problem: a system mired in financial rent-seeking by super-rich elites and geared to boom, bust and speculation, with an ever-greater fiscal hangover limiting public investment and growth. To these problems, which are the source of radicalisation to the left, Collier’s solutions are timid. Yet the central call of Collier’s book – for a return to ethics in policymaking – is welcome. For as Tim Rogan points out in The Moral Economists, it is remarkable how unmoral the left’s critique of capitalism has become. Across the developed world the dysfunctions of free-market economics are seen as negative material outcomes: rising inequality, low growth and poor social mobility. While the left’s emphasis on material inequality seems unremarkable, says Rogan, “in historical perspective it is extraordinary… An alternative tradition focused less on material outcomes than on moral or spiritual consequences has fallen into disuse.” Surveying the work of Tawney, Polanyi and Thompson, Rogan shows how the 20th-century moral critique of capitalism was rooted in humanism, in part derived from the Judeo-Christian religions, and in part from their last prophet – the early Marx. The attack on humanism after the 1960s, first by structuralist Marxism and then by postmodernism, stripped the left’s moral critique of capitalism of its confidence. For the followers of Louis Althusser, history was a “process without a subject”. The downsides of capitalism had to be calculated functionally – in terms of the rising technology clashing with old forms of social organisation – and not against the moral claim of working-class people to a fully human life, which was seen as a hangover from Christian socialism. Each of the theorists Rogan surveys studied the transition from late feudalism to early capitalism, observing the death of a pre-capitalist moral universe as industrialisation and commerce introduced utilitarian ethics to the masses. Each also observed among the 20th-century working class a surviving moral critique of capitalism and an alternative moral practice: Tawney found it in the everyday solidarity of his contemporaries in the Potteries; Thompson in the literate and cultured lives of the 19th-century pioneers of labour he studied in The Making of the English Working Class (1963). Each, in turn, tried to ground this plebeian moral alternative in something theoretical: for Tawney it was Christian socialism, for Polanyi a rereading of Adam Smith and for Thompson the early Marx. Ultimately, Rogan shows, they were all unsuccessful, leaving the ethical framework for 21st-century capitalism open to the forces Collier derides: utilitarianism and Rawlsian justice theory. Which begs the question: what might be the moral basis for a critique of neoliberal capitalism, should anybody beyond a few nostalgics be in the market for it? If we are to judge the Gestapo-like tactics of the Department for Work and Pensions, the actions of Brett Kavanaugh, or Duterte’s death squads in the Philippines as merely dysfunctional to the operation of the free market and the rule of law, then we don’t need a moral philosophy. The airport bookshelves are groaning with blockbusters insisting humans are “already algorithms”, under the complete control of our DNA and our smart devices, and thus absolved by neuroscience from moral responsibilities founded on human values. For Collier, the biggest mea culpa neoliberalism must deliver is over the destruction of community, without which reciprocal obligations cannot give rise to shared values. But having rejected utilitarianism and social justice, Collier never suggests what the source of a new shared value system might be, other than a spontaneous mass return to the thought-patterns and behaviours of his home town, Sheffield, in the 1960s. People shaped by 30 years of compliance with neoliberalism, for whom freedom has come to mean the ability to choose between latte and cappuccino, cannot return to the value systems of their grandparents. A new moral critique of capitalism would have to be based on a shared concept of the human rights accruing to an adult with a smartphone, a credit card and a Tinder account. The networked generation, written off as amoralists and rent-seekers by Collier, are in fact engaged intensely in questions of practical morality, above all via the agony columns and private social networks of advice. Is it right to “ghost” somebody you slept with but didn’t like? Can polyamory work without someone getting exploited? Can you snort cocaine without becoming complicit in the destruction of rainforests? Though these questions sound facile to the older generation, they should be read as evidence that the young generation is searching for an alternative morality, albeit in a largely godless world. Among the networked social movements of the past ten years, from the British student revolt in late 2010, via Greece and Turkey, through to #MeToo and Corbynism, I’ve found an implicit moral critique of capitalism amounting to this: it dulls human potential, requires absurd levels of performative behaviour, and makes you unhappy. Though that is not the same critique as the one Tawney found in Staffordshire, or Polanyi in 1920s Red Vienna, it is an implicit moral system none the less, and rooted the same desire to live a fully human life. Looked at this way, the networked individuality that characterises the new demos of the 21st century is something more than selfish amoralism. This group, too, can generate oppositional movements, ideologies and projects. It, too, can be communitarian: witness any music festival, or rave, or just a beach such as Brighton or Bondi on a really busy summer’s day. If so, the 21st century will not play out as a battle between the emotionalism of the extremes versus the pragmatism of the centre. It will be a struggle over which moral critique of neoliberalism wins. In that struggle, a truly “hard centre” would make a choice: to ally with the left, with the radical movements inspired by Corbyn, Mélenchon and Sanders, against the fascists, misogynists and xenophobes, wallowing in nostalgia. It’s a choice modern centrism seems determined to avoid making. Paul Mason’s “Clear Bright Future: A Radical Defence of the Human Being” will be published next year by Allen Lane The Future of Capitalism: Facing the New Anxieties Paul Collier Allen Lane, 256pp, £20 The Moral Economists: RH Tawney, Karl Polanyi, EP Thompson, and the Critique of Capitalism Tim Rogan Princeton University Press, 280pp, £30
N/A
Keywords: MORAL Economists: R.H. Tawney; Karl Polanyi; E.P. Thompson & the Critique of Capitalism; The (Book); book review

Polanyi, the Failed Prophet of Moral Economics - Adelman, Jeremy (Boston Review, 2017)
Polanyi gave us a vital counterpoint to the hegemony of political economics. But how far can he take us?
N/A
Keywords: biography; critique

An Economic Prophet for Our Time - Iber, Patrick (The Chronicle of Higher Education, 2017)
Karl Polanyi knew the market couldn’t solve all ills. History is proving him correct.
History; Education
Keywords: Karl Polanyi: A Life on the Left (Book); SANDERS; Bernie; TRUMP; Donald

Karl Polanyi, The Great Transformation and a New Political Economy - Watson, Matthew; Holmes, Christopher; Clift, Ben (brunobertez, 2017)
Karl Polanyi, The Great Transformation and a new political economy Professor Matthew Watson, Assistant Professor Christopher Holmes and Professor Ben Clift, Politics and International Studies Avert…
Political Science; International Relations
Keywords: Great Transformation; The (Book); HAYEK; Friedrich A. von (Friedrich August); 1899-1992; KEYNES; John Maynard; 1883-1946; MARX; Karl; 1818-1883

Polanyi against the whirlwind - Guinan, Joe; Hanna, Thomas M. (Renewal (0968252X), 2017)
The author argues that market liberalism should be stopped if the 21st century generation is to avoid the re-emergence of fascism and environmental collapse. The author calls on the political left to offer a different political economy to avoid the consequences of market liberalism and warns against economist Karl Polanyi's assertion that market liberalism always leads to the erosion of society's human and natural substance. He also discusses the reasons for the political turmoil in the U.S.
N/A
Keywords: environmental monitoring; fascism; liberalism; market liberalism; right & left (political science)

Karl Polanyi and twenty-first century socialism - Block, Fred (openDemocracy, 2016)
Polanyi’s views were the exact opposite of his contemporary, Joseph Schumpeter, who famously defined democracy as giving people a choice over which elite group would rule over them.
Sociology
Keywords: socialism

Karl Polanyi for President - Iber, Patrick; Konczal, Mike (Dissent Magazine, 2016)
Are you a Bernie Sanders supporter? Chances are you'll like Karl Polanyi, too. An explainer.
N/A
Keywords: Great Transformation; The (Book); SANDERS; Bernie

Polanyi In Our Times - Saval, Nikal (The Nation, 2016)
N/A
Keywords: Greek crisis; biography; blog

The Next Safety Net - Colin, Nicolas; Palier, Bruno (2015)
As the economy becomes more automated and digitized, patterns of employment will change dramatically, and social policy will need to evolve too. Instead of relying guaranteed jobs or income, write experts Nicolas Colin and Bruno Palier, governments should embrace the “flexicurity” at the heart of the Nordic model.
N/A
Keywords: automation; economy; employment; flexicurity; robots; safety net; social policy

Karl Polanyi Explains It All - Kuttner, Robert (The American Prospect, 2014)
Want to understand our market-crazed era? Rediscover the 20th century’s most prophetic critic of capitalism.
N/A
Keywords: intellectual biography

Why Karl Polanyi Still Matters - Bollier, David (On the Commons, 2009)
It's a ripe moment to dust off "The Great Transformation" and its anthropological critique of "self-regulating markets."
Interdisciplanary
Keywords: commons

The Commons as a New Sector of Value-Creation - Bollier, David (Kosmos, 2008)
Let me start with a bit of wisdom I once picked up from Thomas Berry, a historian of cultures who has said, “The universe is the communion of subjects, not a collection of objects.” This epigraph encapsulates the monumental shift that I believe we are undergoing as we move into a new kind of cultural if not economic reality. This article was originally published in the Fall | Winter 2008 issue of Kosmos Journal. To download a PDF version of this article, please click here.
Interdisciplanary
Keywords: commons

The revenge of ideas: Karl Polanyi and Susan Strange - Halliday, Fred (openDemocracy, 2008)
Political Science
Keywords: STRANGE; Susan

Building a Solidarity Economy in the 21st Century - Lewis, Mike; Conaty, Patrick (Newsletter of the North American Network for the Solidarity Economy, 2004)
"If we don't set out a stronger theoretical base for our work, if the movements we build are simply pragmatic & without a sound intellectual base, we will not succeed in changing hearts and minds." Pat Conaty
N/A
Keywords: solidarity economy

A Karl Polanyi Revival - Mendell, Marjorie (Canadian Dimension, 2001)
Presents insights from the book 'The Great Transformation,' by Karl Polanyi. Concerns that the economic benefits of globalization override political and social costs; Polanyi's vision of democratic socialism not coordinated by central planners; Research into the origins of economic institutions.
N/A
Keywords: Great Transformation; The (Book); economics - research